The Influence of Shiritory Game toward Improvement the Students’ Vocabulary at MTS DDI Ujung Lare Parepare - Nanning Nanning; Nurasiza Nurasiza; Abd. Rauf Ibrahim (EDUVELOP, 2018)
This research is based on two major points namely fulfilling the students’ need regards English vocabulary ability and on how to attract the students to be active in learning process by using media. The objectives of the research are to find out whether or not the use of shiritory game can improve the vocabulary mastery of the eight year students of MTs DDI Ujung Lare Parepare and to know the use of Shiritory Game as learning media in improving the activeness of the eight year students of MTs DDI Ujung Lare Parepare in English learning process. Besides, this research is expected can be useful reference for those who want to use media in their teaching and learning process. In this research the researcher applied class experimental design, with two classes, experiment and control class. In one class consist of four meetings. The samples of the research were 20 students from Class VIII MTs DDI Ujung Lare Parepare. After analyzing the research data, this research revealed the mean score of the students before giving treatment which reached 7.55. After giving treatment, their vocabulary mastery has increase, this was proved with the mean score 15.45. The data after pretest and posttest between experiment and control group showed that the using of Shiritory game has been influenced the students’ achievement with significance Sig Value=0.020<0.05. Comparing with conventional games, Shiritori game is better in improving students’ achievement in learning vocabulary because Shiritori game may increase students’ concentration in playing it, also increase students in memorizing and spelling more new vocabularies and also make them enjoyable, fun and competitive in doing this games. It means that the using of Shiritory games has a good influence in students’ learning since it helping students to develop their English language abilities.